Challenges of administering OPRAS in district councils in Tanzania: The case of Lushoto district council - Mwanaamani, Mtoo (Mzumbe University, 2024)
A dissertation submitted in partial fulfilment of the requirement for award of the Degree of Master of Public Administration (MPA) of Mzumbe University